Up-Link/Down-Link capacity Unbalance analysis in UMTS using a GIS based Planning Tool and MATLAB simulation (2003)
Capacity analysis using simulation is not a new thing in literature. Most of the development process of UMTS standardization have used simulation tools; however, we thing that the use of GIS planning tools and matrix manipulation capacity of MATLAB can show us different scenarios and make a more realistic analysis. Some work is been doing in COST 273 in order to have more realistic scenarios for UMTS planning. Our work initially was centered in uplink analysis, but we are now working in downlink analysis, specifically in two areas: capacity in number of users for RT and NRT services, and Node B power. In this work we will show results for up-link capacity and some results for downlink capacity and BS power consumption.